Pharmaceutical equivalence of metformin tablets with various binders - L.C. Block; L.O. Schemling; A.G. Couto; S.C. Mourão; T.M.B. Bresolin (São Paulo State University (UNESP), 2008)
Metformin hydrochloride is a high-dose drug widely used as an oral anti-hyperglycemic agent. As it is highly crystalline and has poor compaction properties, it is difficult to form tablets by direct compression. The aim of this study was to develop adequate metformin tablets, pharmaceutically equivalent to the reference product, Glucophage® (marketed as Glifage® in Brazil). Metformin 500mg tablets were produced by wet granulation with various binders (A = starch, B = starch 1500®, C = PVP K30®, D = PVP K90®). The tablets were analyzed for their hardness, friability, disintegration, dissolution, content uniformity and dissolution profile (basket apparatus at 50 rpm, pH 6.8 phosphate buffer). The 4 formulations, F1 (5% A and 5% C), F2 (5% B and 5% C), F3 (10% C) and F4 (5% D), demonstrated adequate uniformity of content, hardness, friability, disintegration and total drug dissolution after 30 minutes (F1, F2 and F4), and after 60 minutes (F3). The drug release time profiles fitted a Higuchi model (F1, F2 and F3), similarly to the pharmaceutical reference, or a zero order model (F4). The dissolution efficiency for all the formulations was 75%, except for F3 (45%). F1 and F2 were thus equivalent to Glifage®.